Pelaksanaan Supervisi Kepala Sekolah Di SMP Kristen Elim Makassar - Diana Padang Allo; Ismail Tolla; Ansar Ansar (EDUSTUDENT: Jurnal Ilmiah Pendidikan dan Pembelajaran, 2022)
AbstractThe purpose of this study is 1) to find out the picture of the implementation of the principal's academic supervision and 2) to find out the supporting factors and inhibiting factors for implementing the principal's academic supervision. This research approach is qualitative. The data sources in this study are principals and teachers of the field of study. Data collection techniques through interviews, observation, and documentation. Data analysis through data reduction, data presentation, and concluding. The results of this study show that the implementation of academic supervision carried out by the principal first carried out the planning process, such as making learning tools (syllabus and rpp), supervision schedules, supervision instruments, supervision techniques, guiding teachers in carrying out learning activities in class or the field, determining the plan for the implementation of supervision and making a supervision format. The principal informs all teachers to prepare all that will be supervised. The implementation of supervision begins with data collection to find various shortcomings and weaknesses of teachers, carried out at the end of the semester, after the midterm exam. The follow-up to the implementation of the principal's supervision is to guide teachers to improve learning by providing examples, discussions, training, and consultations. Supporting factors are the readiness of teachers to receive guidance, the willingness of teachers to participate in supervision, and inhibiting factors, namely, teachers who do not prepare themselves, and all administrative components become obstacles in the implementation of academic supervision